Peran Brand Image Sebagai Mediator Dalam Pengaruh Word Of Mouth Terhadap Purchase Intention: Studi Kasus Produk Mie Sedaap Korean Spicy Chicken Di Kota Tangerang - Martin Martin; Adryan Rachman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study was conducted to evaluate the effectiveness of brand image in mediating the impact of word of mouth (WOM) on the desire to purchase Mie Sedaap Korean Spicy Chicken products in the Tangerang City area. Through a survey involving 200 individuals selected based on purposive sampling, this research utilized the Partial Least Squares Structural Equation Modeling (PLS-SEM) model to process and analyze the data obtained. The results found indicate a positive impact of WOM on brand image and purchase intention, with brand image also functioning as a significant mediator in linking WOM with purchase intention. The conclusion of these findings underscores the need for effective marketing strategies in utilizing WOM to strengthen brand image, which in turn has the potential to increase purchase intentions among consumers.